The life and adventures of Robinson Crusoe. - Defoe, Daniel 1661?-1731.; Duvoisin, Roger 1900- (Cleveland New York World Pub. Co., 1946)
The diary of an Englishman shipwrecked for almost thirty years on a small isolated island where, using wit and industry, he manages to build life anew.
Map on lining papers.
Keywords: Survival after airplane accidents, shipwrecks, etc. -- Juvenile fiction; Shipwrecks -- Fiction; Survival -- Fiction